Enhancing AquaCrop model precision for accurate simulation of sweet potato and taro landraces - Mthembu, Thando Lwandile; Kunz, Richard; Mabhaudhi, Tafadzwanashe; Gokool, Shaeden (Frontiers in Sustainable Food Systems, 2025)
Neglected and underutilised crop species (NUS) such as orange-fleshed sweet potato (OFSP) and taro are nutrient-dense, climate-resilient crops with high potential to diversify food systems. While the AquaCrop model has been calibrated to simulate canopy cover (CC), biomass, and yield for both crops, independent testing across diverse agro-ecological zones is required to critically assess model robustness. We, therefore, evaluated AquaCrop’s ability to simulate the growth and yield of OFSP and taro at three locations in the KwaZulu-Natal province, South Africa. Critical recalibration adjustments included reducing taro’s maximum rooting depth, modifying soil water depletion thresholds to better reflect water stress, and parameterising phenology based on tuber mass stabilisation. Recalibration improved model performance for CC (R2, coefficient of determination, up to 0.954 for OFSP; 0.632 for taro), biomass (NSE, Nash-Sutcliffe efficiency, up to 0.975), and final yield (absolute deviations ≤ 6% under optimal irrigation). Validation across three locations confirmed that AquaCrop reliably simulates growth and yield under non-stressed conditions, although performance declined under water-limited environments. The model was run in growing degree-day mode to account for climate variability, which is recommended for future validations. These results demonstrate that, with high-quality calibration datasets representing multiple landraces, AquaCrop can provide reliable yield predictions for NUS. This enables more accurate water management, operational yield predictions, and climate risk assessments for both smallholder and commercial farmers. By bridging the modelling gap for NUS, this work supports their integration into climate adaptation strategies, strengthens food and nutrition security, and promotes resilient agricultural diversification under variable climatic conditions.